Well-being at school : a social problem - Martin, Claude, 1955-; Diter, Kevin (ISTE Ltd ; John Wiley & Sons, Inc., 2024)
In recent decades, children's well-being, particularly at school, has become a major political and academic issue that has gained importance both in public policy and in the social sciences. Well-being at School uncovers and discusses the different ways in which school well-being has been defined and evaluated, by outlining the international and interdisciplinary state of the art. It presents recent and diversified empirical evidence in different European and non-European countries, which bring together perspectives that have often been arbitrarily and artificially opposed in the literature: objective well-being versus subjective well-being; adult-centered perspective versus child-centered perspective; and analysis of family determinants versus analysis of school determinants of child well-being. This book's originality lies in simultaneously considering the multiple dimensions of children's well-being at school and understanding how these different determinants interact and combine, depending on the (geographical, social and family) contexts in which the children live.
Keywords: School psychology.; Well-being.; elektronické knihy; electronic books